PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH PESERTA DIDIK KELAS X SMAN 1 LUBUK SIKAPING - Rahma Yulvira (Jurnal Edukasi dan Penelitian Matematika, 2022)
Mathematical problem solving is an ability that must develop in learning mathematics. That is because, with the development of problem solving ability, the mindset of students will also increase. But in reality, the problem-solving ability of the 10th-grade students of SMAN 1 Lubuk Sikaping is still relatively low. Therefore, the study applied the model Problem-Based Learning to improve student’s problem-solving ability. The type of research is pre-experimental with the one-shot class study design. The study subjects were all of the 10th-grade SMAN 1 Lubuk Sikaping for the 2021/2022 year. The results data obtained from quiz and test mathematical's problem-solving abilities. Thus, it concluded that the learning Problem Based Learning positively influenced the mathematical problem solving ability of the 10th grade of SMAN 1 Lubuk Sikaping. Keywords — Problem Solving, Problem Based Learning